The Relationship between Gender Gap in Employment and Hofstede’s Culture Dimensions depending on Country Scores - Hilal Terzi; Fatih Özdemir; Türker Özkan (Psikoloji Çalışmaları)
Why is there a significant gender gap in the global labor force participation? Is there a way to reduce vulnerable employment? May cultural values explain the gender gap in employment and male-dominant work structure? This research examined the associations between Hofstede’s culture dimensions (including power distance, individualism, masculinity, uncertainty avoidance, and long-term orientation) and gender gap in employment indicators (women’s and men’s labor force participation and vulnerable employment rates) after controlling the economy. Secondary data were obtained from Hofstede’s culture dimensions and World Bank databases. When the countries with missing data are excluded, remaining data of 60 countries make up the data set of the study. Two-step hierarchical regression analyses were performed, in which economic development was entered in the first step and study variables were included in the model in the second step. The main results indicated that after controlling economic development, women’s labor force participation rate was negatively related to country scores on uncertainty avoidance. In contrast, men’s labor force participation rate was negatively associated with country scores on power distance, individualism, and uncertainty avoidance. Besides, both women’s and men’s vulnerable employment rates were negatively related to country scores on individualism. The fact that more women and men participate in the labor force in countries with low power distance and uncertainty avoidance can be interpreted as women’s labor force participation creates new job opportunities that both women and men benefit from. The results may be useful for researchers who aim to see the current gender-based labor force participation patterns in different countries and understand the culture dynamics of economic gender gap.